Pengaruh Strategi Pembelajaran dan Self-Efficacy terhadap Pengetahuan Siswa Tentang Konsep Dasar Ekologi - Semuel Sanda Patampang (Universitas Negeri Jakarta, 2017)
The purpose of this research is to know the effect of instructional strategy and self-efficacy of the students’ knowledge about basic concepts of ecology. This research uses an experimental method to design treatment by level 2 X 2 on the class X of the Senior High School 3 Palu. Sample of 48 students, selected using multistage random sampling, and are divided into groups. The results: (1) Knowledge of the basic concepts of ecology in students group taught instructional strategy inductive is higher, than that taught instructional strategy deductive; (2) For a students group who have high self-efficacy, to the knowledge of the basic concepts of ecology, taught instructional strategy inductive is higher, than that taught instructional strategy deductive; (3) For a students group who have low self-efficacy, to the knowledge of basic concepts of ecology, taught instructional strategy deductive is higher, than that taught instructional strategy inductive; and (4) There is an interaction effect between instructional strategy and self-efficacy of the students’ knowledge about basic concepts of ecology. From this research, it was found that the students group who have high self-efficacy, to the knowledge of the basic concepts of ecology better taught instructional strategy inductive, while in the students group have low self-efficacy better taught instructional strategy deductive.